Evaluating and prioritizing the risks of BOT projects using structural equations and integrated model of fuzzy AHP and fuzzy TOPSIS - Seyed Morteza Hatefi (Iranian Society of Structrual Engineering (ISSE), 2019)
The private sector has an important role on the development of cities, and governments are encouraging this sector to implement civilian projects. The BOT approach is one of the ways that increases private sector participation in government infrastructure development. Today, paying attention to the financing of urban projects and new financing approaches, including the BOT approach, is necessity in most of the major cities, especially in Tehran. But it is necessary to use the BOT method to address and understand all the dimensions and issues behind the implementation of this method. In many cases, failure to complete the projects in due time is due to the lack of proper management of the project, which results from a lack of understanding of the risks involved in these projects. Therefore, assessment and prioritization of risks in BOT projects, especially when the number of risk factors increases, is considered as an important part of the complex risk management process. In this paper, the method of structural equations and integrated model of fuzzy AHP and fuzzy TOPSIS are used to evaluate and prioritize the risks in Tehran Municipality's development projects that are implemented in the form of BOT contract method. Structural equations are used to measure the validity of identified risks. The fuzzy AHP method is used to determine the weight of the risk assessment criteria and the fuzzy TOPSIS method is utilized to evaluate and prioritize the risks of BOT projects. The results indicate that the risk of commodity price fluctuations, the risk of rising inflation, the risk of exchange rate fluctuations, and the risk of non-application of techniques and project management knowledge are the most important risks in BOT projects.